Estudo de formulação de massa para aplicação em placas cerâmicas - Pinto, Rogério César de Almeida (2010)
The sector of civil construction is strongly related to the red ceramic industry. This sector uses clay as raw material for manufacturing of various products such as ceramic plates. In this study, two types of clay called clay 1 and clay 2 were collected on deposit in Ielmo Marinho city (RN) and then characterized by thermogravimetric analysis (TG/DTG), differential thermal analysis (DTA), X-ray diffraction (XRD), X-ray fluorescence (XRF), rational analysis and particle size distribution and dilatometric analyses. Ceramic plates were manufactured by uniaxial pressing and by extrusion. The plates obtained by pressing were produced from the four formulations called 1, 2, 3 and 4, which presented, respectively, the following proportions by mass: 66.5% clay 1 and 33.5% clay 2, 50% clay 1 and 50% clay 2, 33.5% clay 1 and 66.5% clay 2, 25% clay 1 and 75% clay 2. After firing at 850, 950 and 1050 °C with heating rate of 10 °C/min and soaking time of 30 minutes, the following technological properties were determined: linear firing shrinkage, water absorption, apparent porosity, apparent specific mass and tensile strength (3 points). The formulation containing 25% clay 1 produced plates with most satisfactory results of water absorption and mechanical resistance, because of that it was chosen for manufacturing plates by extrusion. A single firing cycle was established for these plates, which took place as follow: heating rate of 2 °C/min up to 600 ºC with soaking time of 60 minutes, followed by heating using the same rate up to 1050 ºC with soaking time of 30 minutes. After this cycle, the same technological properties investigated in the plates obtained by pressing were determined. The results indicate (according to NRB 13818/1997) that the plates obtained by pressing from the mixture containing 25 wt% clay 1, after firing at 1050 °C, reach the specifications for semi-porous coating (BIIb). On the other hand, the plates obtained by extrusion were classified as semi-stoneware (group AIIa)